Future teachers training in selection and application of interactive electronic content - Kuvshinova E. N. (Educational environment today: development strategies, 2016)
this article deals with the task of preparing future teachers to ensure the basic educational program of educational-methodical and information support, presents the interactive electronic content according to the requirements of the Federal educational standard of basic general education
Keywords: информационное взаимодействие; интерактивный электронный контент; interactive electronic content; information interaction